Apocalypse Now: Australian Bushfires and the Future of Urban Settlements - Norman, Barbara; Newman, Peter; Steffen, Will (Nature, 2021)
The apocalyptic Australian bushfires have challenged the way we plan settlements. What is the future for small urban settlements within fire-vulnerable forests and bushland? Could they create a new model for rural settlements with wider lessons for development in big cities? This paper draws together observations of the 2019/20 bushfire size, intensity and destructiveness and links the fires to the global nature of the climate crisis and an earlier case study that accurately predicted the fire impacts in southeast coastal Australia. The findings are set out in two scenarios suggesting that the fires can lead to a new model for climate resilient development that can flow into larger centres with multiple benefits.